Potential for Reducing CO2 Emissions in the Operation of Subcritical Power Plants into Supercritical - Sunaryo Sunaryo; Arinan Putra; Arief Marwanto; Muhamad Haddin (IAES Indonesia Section, 2020)
The consumption of electricity that increase anytime, also increases CO2 emissions in the air as a result of coal combustion flue gas at the power plant. The operation of supercritical boilers on the power plant will lead to higher thermal efficiency compared to subcritical boilers. Higher steam pressure boiler will increase the thermal efficiency and automatically reduce CO2 emissions due to a reduction in fuel consumption at the same boiler efficiency and heating value of coal. At 166.9 bar subcritical steam boiler thermal efficiency was 45.47 % and CO2 emissions were 602.2 tons while at supercritical pressure 240 bar, efficiency increased to 47.12 % with a reduction in CO2 emissions of 20.9 tons to 581.3 tons.